Signal pathways involved in contrast-induced acute kidney injury - Deng, Ke; Pei, Mingxin; Li, Beibei; Yang, Nanqi; Wang, Zijian; Wan, Xinchi; Zhong, Zhiying; Yang, Zhiyi; Chen, Yanling (Frontiers in Physiology, 2024)
Contrast-induced acute kidney injury (CI-AKI) has emerged as a global public health concern, ranking as the third most prevalent cause of hospital-acquired acute kidney injury, which is related to adverse outcomes. However, its precise pathogenesis remains elusive. Consequently, researchers are dedicated to uncovering CI-AKI’s pathophysiology and signaling pathways, including inflammation, oxidative stress, apoptosis, and ferroptosis, to improve prevention and treatment. This review thoroughly analyzes the signaling pathways and their interactions associated with CI-AKI, assesses the impact of various research models on pathway analysis, and explores more precise targeted treatment and prevention approaches. Aims to furnish a robust theoretical foundation for the molecular mechanisms underpinning clinical treatments.